The financial crisis and lower income countries: A preliminary synthesis of findings on impacts, responses and lessons - Sam Jones (Danish Institute for International Studies (DIIS), 2010)
This paper synthesizes findings from a range of studies presented at a recent conference on the financial crisis held at the Danish Institute for International Studies (DIIS). Focusing on low and lower-middle income countries, the studies explore the impacts, responses and initial lessons of the crisis. The complex and diverse nature of these impacts at both the aggregate and household levels are highlighted, as is the need to reconsider conventional policy advice. Considerations for future research directions are also presented.
Keywords: 330